1995
DOI: 10.1093/jn/125.9.2417
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium Absorption from the Colon and Rectum Are Increased in Rats Fed Fructooligosaccharides

Abstract: We investigated the effects of fructooligosaccharides on the absorption of calcium, magnesium and water from the colon and rectum of rats fed a control diet or the control diet containing 50 g fructooligosaccharides/kg. Chromium-mordanted cellulose was used as an unabsorbable marker to calculate apparent absorption of calcium and magnesium. There was a positive correlation (r = 0.982, P < 0.001 in rats fed the control diet and r = 0.975, P < 0.001 in rats fed the fructooligosaccharides-containing diet) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
1
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(123 citation statements)
references
References 19 publications
11
106
1
5
Order By: Relevance
“…This is the ®rst time, to our knowledge, that such an effect has been observed in humans. These results con®rm previously reported data from animal investigations in our own laboratory, (Demigne  et al, 1989;Levrat et al, 1991;Younes et al, 1996), and by other workers (Delzenne et al, 1995;Ohta et al, 1995). Several hypothesis about the mechanisms of the effect of inulin on Ca absorption could be proposed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is the ®rst time, to our knowledge, that such an effect has been observed in humans. These results con®rm previously reported data from animal investigations in our own laboratory, (Demigne  et al, 1989;Levrat et al, 1991;Younes et al, 1996), and by other workers (Delzenne et al, 1995;Ohta et al, 1995). Several hypothesis about the mechanisms of the effect of inulin on Ca absorption could be proposed.…”
Section: Discussionsupporting
confidence: 91%
“…In our laboratory, we showed that inulin enhanced Ca and Mg absorption in animal studies (Demigne  et al, 1989;Levrat et al, 1991). This observation was recently con®rmed by other workers also in animal studies (Delzenne et al, 1995;Ohta et al, 1995). Unfortunately, limited information is available for humans, and only indirect evidence that this effect could occur in humans has been reported (Trinidad et al, 1993(Trinidad et al, , 1996.…”
Section: Introductionmentioning
confidence: 53%
“…The final concentration of hematocrit (eight weeks) in the rats with gastrectomy was not different from the sham-operated rats fed with any one of the diets (Figure 1). Similar effects have also shown by other researchers for other prebiotics [19][20][21][22] .…”
Section: Fecal Iron and Apparent Iron Absorptionsupporting
confidence: 90%
“…In this respect, it is important to point out that there is a substantial positive correlation between the concentration of serum iron and the absorption of iron. Studies with fructooligosaccharides also presented an increased absorption of iron in deficient rats iron deficiency 19 , suggesting that this diet could prevent the anemia.…”
Section: Fecal Iron and Apparent Iron Absorptionmentioning
confidence: 94%
“…As an effect of fermentation, the reduction in pH occurs as the result of stimulated production of lactic acid and short-chain fatty acids, mainly propionate, acetate and butyrate [30]. At lower pH, more mineral is soluble in the gut lumen and thus is more readily absorbed from the gut mucosa cell [31]. Apart from indirect stimulation of minerals absorption by increasing its solubility via lowering the pH, short-chain fatty acids can also directly influence its bioavailability by complexing with the minerals leading to an increase in their absorption.…”
Section: Introductionmentioning
confidence: 99%